2008
DOI: 10.1242/jeb.018960
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of p38-MAPK and JNKs in mediating early protection or apoptosis in the hyperthermic perfused amphibian heart

Abstract: SUMMARYIn the present study the activation of p38 mitogen-activated protein kinase (p38-MAPK) and c-Jun N-terminal kinases (JNKs) by hyperthermia was investigated in the isolated perfused Rana ridibunda heart. Hyperthermia (42°C) was found to profoundly stimulate p38-MAPK phosphorylation within 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 56 publications
5
23
0
Order By: Relevance
“…These results indicated that the MAPK pathway was potentially involved in transducing the signals from extracellular stimuli to the nucleus for transcriptional changes and consequent induction of apoptosis. JNK and p38-MAPK are well-known stress-activated protein kinases that evoke sequential interactions related to cell death or survival [50]. In particular, p38 is also a marker of oxidative stress, which increases the phosphorylation levels of p38 [44, 51], consistent with our findings and supporting the claim that oxidative stress is involved in the mechanism underlying the combined treatment.…”
Section: Discussionsupporting
confidence: 90%
“…These results indicated that the MAPK pathway was potentially involved in transducing the signals from extracellular stimuli to the nucleus for transcriptional changes and consequent induction of apoptosis. JNK and p38-MAPK are well-known stress-activated protein kinases that evoke sequential interactions related to cell death or survival [50]. In particular, p38 is also a marker of oxidative stress, which increases the phosphorylation levels of p38 [44, 51], consistent with our findings and supporting the claim that oxidative stress is involved in the mechanism underlying the combined treatment.…”
Section: Discussionsupporting
confidence: 90%
“…What is more, the observed sustained activation of p38-MAPK could underscore the critical role of this kinase under the interventions investigated. Such a hypothesis may be justified as activation of p38-MAPK has been shown to exert a beneficial role in various experimental models exposed to stressful conditions (Lavoie et al, 1995;Clerk et al, 1998) as well as in the isolated perfused amphibian heart subjected to hyperthermia (Gaitanaki et al, 2008). Nevertheless, no data are available so far regarding the potential effect of p38-MAPK on the modulation of gene expression in mussels.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, in an effort to evaluate the biological impact of hyperthermia in mussels and with heat stress known to favour apoptosis (Gaitanaki et al, 2008;Bellmann et al, 2009), we assessed the occurrence of apoptosis. Detection of cleaved fragments of PARP by immunoblotting 8h after the onset of hyperthermia (Fig.2B) substantiated the delayed initiation of the apoptotic process, which also explains the high mortality rate for mussels observed after exposure to 30°C for 24h.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of M. galloprovincialis to 30°C was found to cause a significant and sustained stimulation of p38-MAPK phosphorylation while the activation profile of JNKs was transient and relatively moderate in gill tissue (Gourgou et al, 2010;Evans and Somero, 2010). It was demonstrated that p38-MAPK phosphorylation was activated more rapidly and strongly than that of JNKs in the isolated perfused heart of the frog Rana ridibunda at 42°C (Gaitanaki et al, 2008), further indicating that p38 and JNKs might play different roles in animals during temperature stress.…”
Section: Stress-signaling Proteinsmentioning
confidence: 94%